2004
DOI: 10.1039/b404268a
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic reduction of aromatic azides to amines using CdS and CdSe nanoparticles

Abstract: We have shown that CdS and CdSe nanoparticles can act as very efficient and highly chemoselective photocatalysts for the reduction of aromatic azides to aromatic amines. In several cases, the reaction proceeds with quantum yields near 0.5, which approaches the theoretical maximum for a two-electron process. The wide scope of the reaction was confirmed with compounds containing electron withdrawing (-NO(2), CO(2)R, COR) and electron donating groups (-OMe, -R, -Cl) at the para-, meta-, and ortho-positions. Remar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 48 publications
(11 reference statements)
0
33
0
Order By: Relevance
“…CdS nanoparticles have a photocatalytic effect on the reduction of aromatic azides to form aromatic amines in water (Scheme 9b). [37] With the existence of some other functional groups on the aromatic ring, the products can be maintained in high selectivities. Furthermore, the position of substituent has slight influence on the reaction.…”
Section: Binary and Ternary Metal Sulfidesmentioning
confidence: 99%
“…CdS nanoparticles have a photocatalytic effect on the reduction of aromatic azides to form aromatic amines in water (Scheme 9b). [37] With the existence of some other functional groups on the aromatic ring, the products can be maintained in high selectivities. Furthermore, the position of substituent has slight influence on the reaction.…”
Section: Binary and Ternary Metal Sulfidesmentioning
confidence: 99%
“…In these cases, CdS nanorods or nanowires have been synthesized in ethylenediamine (en) by solvothermal conditions at high temperature (120-200°C) and long aging time (5-24 h) [15][16][17][18][19]. In addition, high activities of CdS in photocatalytic reduction reactions have been also reported [20,21]. In this way, in recent works we have studied the influence of the ethylenediamine (en) on the photoreducting properties of CdS nanorod for 4-nitrophenol reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Miguel and co-workers, for example, applied CdS and CdSe QDs in the photocatalytic reduction of aromatic azides to amines. [4] Niemeyer and Ipe employed QD/enzyme nanohybrids for photocatalyzing the transformation of myristic acid to a-and b-hydroxymyristic acid. [5] Most recently, Ford and co-workers found that 1,1-dithiooxalate bound to the surfaces of CdSe QDs can be converted into carbon disulfide under aerobic conditions through oxidative cleavage.…”
mentioning
confidence: 99%